2021
DOI: 10.3390/cells10092220
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Regulation and Pharmacological Modulation of Sepsis-Induced HMGB1 Release and Action: An Updated Review

Abstract: Sepsis remains a common cause of death in intensive care units, accounting for approximately 20% of total deaths worldwide. Its pathogenesis is partly attributable to dysregulated inflammatory responses to bacterial endotoxins (such as lipopolysaccharide, LPS), which stimulate innate immune cells to sequentially release early cytokines (such as tumor necrosis factor (TNF) and interferons (IFNs))and late mediators (such as high-mobility group box 1, HMGB1). Despite difficulties in translating mechanistic insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 194 publications
(282 reference statements)
0
14
0
Order By: Relevance
“…In response to hepatic I/R, liver resident Kupffer cells and infiltrated neutrophils orchestrate rigorous inflammatory responses manifested by the production of ROS, RNS, chemokines, and cytokines that collectively contribute to hepatic injury (1)(2)(3). Consequently, hepatocellular injury caused the passive release of DAMPs such as CIRP ( 5) and HMGB1 (6,7), which further stimulate a feed-forward cycle of inflammatory injuries (8, 9) (Figure 7). In response to injury, a neutrophilic CXC chemokine, MIP-2, can be produced by macrophages and hepatocytes, and facilitate neutrophil recruitment and activation (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to hepatic I/R, liver resident Kupffer cells and infiltrated neutrophils orchestrate rigorous inflammatory responses manifested by the production of ROS, RNS, chemokines, and cytokines that collectively contribute to hepatic injury (1)(2)(3). Consequently, hepatocellular injury caused the passive release of DAMPs such as CIRP ( 5) and HMGB1 (6,7), which further stimulate a feed-forward cycle of inflammatory injuries (8, 9) (Figure 7). In response to injury, a neutrophilic CXC chemokine, MIP-2, can be produced by macrophages and hepatocytes, and facilitate neutrophil recruitment and activation (44).…”
Section: Discussionmentioning
confidence: 99%
“…This process exerts direct but moderate hepatic injury, and facilitates the infiltration of neutrophils, which release more ROS and proteases to exacerbate a cascade of inflammatory injury (2,3). Furthermore, the generation of ROS and RNS also leads to hepatocellular death (2,4) and consequent release of damageassociated molecular patterns (DAMPs) such as cold-inducible RNA-binding protein (CIRP) (5) and high mobility group box 1 (HMGB1) (6,7). We and others have shown that HMGB1 (8) and CIRP (9) exacerbate liver damage in animal models of hepatic I/R, as these DAMPs can amplify a cascade of oxidative and inflammatory responses during a late stage of reperfusion (1,10).…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of its functional facets is now largely extended ( 22 ). For example in the context of septic shock, its determinant impact has been early observed since HMGB1 injection was fatal whereas its neutralization by antibodies could rescue mice challenged with LPS ( 23 25 ). Extracellular HMGB1 is therefore recognized as one of the DAMPs which act as major mediators in immunity ( 26 ).…”
Section: Molecular Bases On Complement and Hmgb1 Multiple Functions W...mentioning
confidence: 99%
“…In addition to being located in the nucleus, HMGB1 can also be present in other organelles as well as in the extracellular space to regulate multiple cell processes ( Lotze and Tracey, 2005 ). Specifically, HMGB1 can be secreted or released by stressed, dead, or dying cells ( Wang et al, 1999 ; Scaffidi et al, 2002 ; Zhu et al, 2021 ; Chen et al, 2022 ). Once released, HMGB1 acts as a damage-associated molecular pattern (DAMP) to trigger immune responses by binding multiple pattern recognition receptors, such as toll-like receptor 4 (TLR4) and advanced glycosylation end product-specific receptor (AGER, also known as RAGE) ( Tsung et al, 2007 ; Kang et al, 2014a ; Amornsupak et al, 2022 ; He et al, 2022 ; Lei et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%